The Role Of The Sociological Researcher In Analyzing The Children Abduction Crime In The Algerian Society - عـمتوت كمال; ديلمي عبد الـعــزيـز (مجلة دراسات في سيكولوجية الانحراف, 2022)
This study aims to determine the role of the sociological researcher in analyzing the child abduction crime in Algerian society based on its description and identifying its characteristics. It also treats the various social, psychological, and economic conditions and factors that directly contribute to its commission and tries to find preventive ways to reduce it. This is our analytical study, in which we have used the descriptive approach. We have concluded through it the necessity of involving all individuals, families, civil society associations, official institutions, and all relevant bodies in any preventive strategy against child abduction crime to ensure social security